Safety culture in COVID-19 wards during 2020 SARS-COV-2 pandemic. (20th October 2021) - Bianchet, B; Doimo, A; Moretti, V; Bellomo, F; Degan, S; Farneti, F; Cocconi, R
Abstract: Background: Safety of care is an essential aim of a healthcare system, even during a pandemic. Incident reporting (IR) is an important safety tool to identify system failures. This study evaluates the impact of SARS-COV-2 pandemic on IR trend in the COVID-19 wards of an Italian Academic Hospital (AH) in Italy. Methods: The study analyzed the IR submitted by the wards of Infectious Diseases (ID), Intensive Care Unit (ICU), Pneumology (P) and Emergency Room (ER) of the AH of Udine from 2016 to 2020. For each ward, IR of 2020 were compared to IR of 2016-2019 period, expressed as the mean value. The IR's topics of ER unit, classified according to the International Standards of Patient Safety, were compared between 2019 and 2020. Variation in reporting was assessed using Chi-square tests. Results: During 2020, 180 incidents were reported, 81.7% of which submitted by ER unit. Three wards showed a decrease in reporting compared to 2016-2019 period: -18% (7vs8, 5) for ID unit, -26% (16v21, 7) for ICU and -44% (10vs18) for P unit. ER unit, instead, showed a great IR increase (147vs49; +200%). Considering the reporting from 2016 to 2019, 196 out of 389 (50.4%) of IR came from ER unit. Analyzing the difference in reporting in ER unit between 2019 and 2020, the IR topics regarding "Delay in execution and reporting exams" increase from 2 to 21 (p < 0, 05), "Lack of human and/or instrumental resources" from 4 to 29 (p < 0, 05) and "Prevention and Control of Hospital Infectious" from 0 to 13 (p < 0, 05). Conclusions: ER unit showed a higher attitude in reporting than the other considered wards, especially during the COVID-19 period, recognizing IR as an important tool to highlight critical issues. This aspect may reflect the stronger safety culture already present in this unit. SARS-COV-2 pandemic stressed in ER needs of human resources to cope with reorganization determined by COVID-19, rapid covid-test results for the patient's care path definition, implementation of infection control procedures. Key messages: A solid safety culture may contribute to maintain high levels of IR even while during challenging times for healthcare systems. Difference in reporting among Covid wards could be explained by a different level of Safety Culture.